Factors Hampering EFL Higher Education Students’ Speaking Ability in the Time of Online Learning - Nur Islah; Anugerah Febrian Syam; Andi Nurhikmah (ELT Worldwide: Journal of English Language Teaching, 2022)
The objective of this study is to investigate the factors that hampered EFL students’ speaking ability in the time of online learning. Descriptive study with a statistical approach undertaken to EFL higher education students as selected participants in this study. Online surveys were employed and analyzed using descriptive statistics. The results revealed two aspects: linguistic and nonlinguistic that impede students’ ability to speak during EFL online learning. On the one hand, the common problem that students face when speaking is related to linguistic aspects covering five indicators: pronunciation, vocabulary, grammar, comprehension, and fluency. In linguistic factor, EFL students mostly experienced difficulty in speaking when dealing with grammar issue, while some students constrained in sentence form and word organization. Linguistic factors become significant obstacle when dealing with speaking ability in EFL online learning. On the other hand, non-linguistic aspects including seven indicators: technology, interaction, lack of self-confidence, fear of making mistakes, anxiety, shyness, and lack of motivation contribute succeeding to constraint EFL students’ speaking ability. In this aspect, technology became the common obstacle of students in speaking. Online learning offers various things comparing to face-to-face learning such as providing appropriate gadget and making sure network bandwidth and connection become a must-have challenge in dealing with online learning. Some students were aware of adapting with meeting conferences applications that cause problems in students’ speaking ability during the period of online learning.